2000
DOI: 10.1073/pnas.011405598
|View full text |Cite
|
Sign up to set email alerts
|

Potent histone deacetylase inhibitors built from trichostatin A and cyclic tetrapeptide antibiotics including trapoxin

Abstract: Trichostatin A (TSA) and trapoxin (TPX) are potent inhibitors of histone deacetylases (HDACs). TSA is proposed to block the catalytic reaction by chelating a zinc ion in the active-site pocket through its hydroxamic acid group. On the other hand, the epoxyketone is suggested to be the functional group of TPX capable of alkylating the enzyme. We synthesized a novel TPX analogue containing a hydroxamic acid instead of the epoxyketone. The hybrid compound cyclic hydroxamic acid-containing peptide (CHAP) 1 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
233
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(245 citation statements)
references
References 28 publications
11
233
0
1
Order By: Relevance
“…In HDAC10, the C-terminal catalytic domain lacks the active pocket residues required for enzymatic activity. The enzymatic activities of HDAC6 and HDAC10 are more resistant to trapoxin and sodium butyrate than those of class I and class IIa HDACs [9,84]. Deletion of the second incomplete catalytic domain of HDAC10 restores its sensitivity to both sodium butyrate and trapoxin, suggesting that the two HDAC domains functionally interact [9].…”
Section: Tigs 54mentioning
confidence: 99%
“…In HDAC10, the C-terminal catalytic domain lacks the active pocket residues required for enzymatic activity. The enzymatic activities of HDAC6 and HDAC10 are more resistant to trapoxin and sodium butyrate than those of class I and class IIa HDACs [9,84]. Deletion of the second incomplete catalytic domain of HDAC10 restores its sensitivity to both sodium butyrate and trapoxin, suggesting that the two HDAC domains functionally interact [9].…”
Section: Tigs 54mentioning
confidence: 99%
“…This would be much easier than using immunoprecipitated subtypes and a nonselective substrate. We compared the subtype selectivities of two TSA-like inhibitors 17 M344 (16b) and M360 (16c) and three structurally unrelated cyclotetrapeptide inhibitors (CHAPs 18,19 ) ( Figure 4). M344 (16b) was selective for HDAC6 vs HDAC1 (IC 50 , 88 vs 249 nM).…”
Section: Synthesismentioning
confidence: 99%
“…Among the more recently synthesized molecules belonging to this class of HDIs are the CHAP compounds, able to exert their inhibitory effect even at nanomolar concentrations (15,16). It has also been shown that newly synthesized sulphonamide hydroxamic acid products were able, at micromolar concentrations, to exert antiproliferative action against human colon tumor cells in vitro (17).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%